Live Confocal Tissue Assessment With SYTO16/PI and WGA Staining Visualizes Acute Organ Damage and Predicts Delayed Graft Function in Kidney Transplantation. Issue 5 (November 2019) - Weissenbacher, Annemarie; Oberhuber, Rupert; Hermann, Martin; Soleiman, Afshin; Ulmer, Hanno; Mayer, Gert; Margreiter, Christian; Maglione, Manuel; Bösmüller, Claudia; Messner, Franka; Resch, Thomas; Cardini, Benno; et al.
Abstract : Objective: The aim of our prospective clinical trial was to test a tissue staining technique (real-time confocal analysis [RTCA]) as a rapid assessment tool for donor kidney quality and function in human kidney transplantation. Summary Background Data: Tools for objective graft tissue viability assessment before kidney transplantation are lacking. RTCA has recently been established and tested in a pilot study using rodent kidneys. Methods: RTCA was performed in kidney biopsies stained with SYTO16/PI and WGA. A score between −3 (100% nonviable) and +3 (100% viable) describes the sum of viable cells divided by the number of nonviable cells per examined area (glomerulus, proximal, and distal tubules). The primary study endpoint was the delayed graft function (DGF). Results: Seventy-one kidney transplant recipients were transplanted. The median recipient and donor age were 58.5 and 57 years, respectively. Cold ischemia time was 13.6 ± 4.7 hours; anastomosis time was 30.8 ± 8.7 minutes (mean ± SD). Overall, 23 (33.8%) patients developed DGF. The RTCA score was significantly lower in kidneys developing DGF −0.43 ± 1.78 versus no DGF 0.91 ± 2.17, P = 0.01. The Remuzzi score did not differ between DGF and no DGF, P = 0.13. Remuzzi score and RTCA score correlate inversely significantly; P = 0.004. In the multivariate analysis, solely RTCA score was revealed as a significant independent factor predicting DGF; P = 0.015, Wald = 5.95, odds ratio = 0.72, 95% confidence interval = 0.55 to 0.94. Conclusions: Our data demonstrate that RTCA is feasible and clinically meaningful. The RTCA score predicts DGF and is a valid option to be applied in renal transplantation.